2010
DOI: 10.2514/1.41776
|View full text |Cite
|
Sign up to set email alerts
|

Microramps Upstream of an Oblique-Shock/Boundary-Layer Interaction

Abstract: To examine the potential of micro vortex generators for shock/boundary-layer interaction control, a detailed experimental and computational study in a supersonic boundary layer at M 3:0 was undertaken. The experiments employed a flat-plate boundary layer with an impinging oblique shock with downstream total-pressure measurements. The moderate Reynolds number of 3800 allowed the computations to use monotone-integrated large eddy simulations. The monotone-integrated large eddy simulations predictions indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 19 publications
(33 reference statements)
4
32
0
Order By: Relevance
“…In set E, three 4 mm micro-ramps were mounted next to each other in the tunnel (see Fig.1(b)). The spacing s between the centre lines of the micro-ramps equals 7.5h = 30 mm, which is the value recommended by Anderson [9] and the one commonly used by other researchers in this field [8,10,11]. Finally, in set F the undisturbed shock wave boundary layer interaction is investigated, which will serve as a reference for all other cases.…”
Section: °7mentioning
confidence: 99%
See 1 more Smart Citation
“…In set E, three 4 mm micro-ramps were mounted next to each other in the tunnel (see Fig.1(b)). The spacing s between the centre lines of the micro-ramps equals 7.5h = 30 mm, which is the value recommended by Anderson [9] and the one commonly used by other researchers in this field [8,10,11]. Finally, in set F the undisturbed shock wave boundary layer interaction is investigated, which will serve as a reference for all other cases.…”
Section: °7mentioning
confidence: 99%
“…The work of Lee [11] showed that RANS computations are not very well suited for these kind of problems and deliver results that deviate significantly from experimental data. Large Eddy Simulations (LES) simulations on the other hand produce results that are much closer to the experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations by Lee et al [11] using implicit large eddy simulation (ILES) described the decay of streamwise velocity component through the cross-sectional contours. A Reynolds-averaged Navier-Stokes (RANS) simulation with immersed-boundary treatment was performed by Ghosh et al [12] (Ma=2.5, h/δ=0.46, 0.92) and the velocity profiles were compared with experiment data [8].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of the micro-ramp have been reported in the preceding researches. A typical application is intended for separation reduction produced in a shock wave/boundary layer interaction (SWBLI) [2][3][4][5][6][7][8] . Although the effects have been demonstrated through the foregoing studies, the flow physics of the microramp has not been fully understood due to the complex geometry of current device.…”
Section: Introductionmentioning
confidence: 99%